Differentiating highly asymmetric keratoconus eyes using a combined Scheimpflug/Placido device. Issue 12 (December 2020) - Golan, Oren; Levinger, Samuel; Barequet, Irit S.; Levinger, Eliya; Varssano, David; Randleman, J. Bradley
Abstract : Corneal tomography can successfully differentiate between 26 unaffected eyes of patients with keratoconus from 166 normal eyes using only 4 metrics related to pachymetry and posterior corneal wall. Abstract : Purpose: To determine the ability to differentiate between normal eyes and clinically unaffected eyes of patients with highly asymmetric keratoconus (AKC) using a Scheimpflug/Placido device. Setting: Tel Aviv Sourasky Medical Center and Enaim Medical Center, Israel. Design: Retrospective case-control. Methods: Imaging from a combined Scheimpflug/Placido device (Sirius, C.S.O.) was obtained from 26 clinically unaffected eyes of patients with frank keratoconus in the fellow eye, and 166 eyes from 166 patients with bilaterally normal corneal examinations that underwent uneventful corneal refractive surgery with at least 1 year of follow-up. Receiver operating characteristic curves were produced to calculate the area under the curve, sensitivity, and specificity of 60 metrics, and finally a logistic regression modeling was used to determine optimal variables to differentiate populations. Results: The most predictive individual metric able to differentiate between 26 eyes in the case group to 166 eye in the control group was the posterior wall inferior-superior (I-S) ratio, with an receiver operating characteristics (ROC) of 0.862. A combination model of 4 metrics (posterior wall I-S ratio in the central 3 mm, thinnest pachymetry coordinate on the x horizontal axis, posterior asymmetry and asphericity index, corneal volume) yielded an ROC of 0.936, with a sensitivity/specificity pair of 92.3%/87%. Variables related to elevation were not found significant. Conclusions: Using a combination of metrics from a combined Scheimpflug/Placido device, a practical model for discrimination between clinically normal eyes of patients with highly AKC and normal eyes was constructed. Variables related to pachymetry and posterior cornea asymmetry were the most impactful.